Solid Particles as Nuclei for Aerosol Formation and Cause of Emissions – Results from the Post-combustion Capture Pilot Plant at Niederaussem. (July 2017) - Moser, Peter; Wiechers, Georg; Stahl, Knut; Stoffregen, Torsten; Vorberg, Gerald; Lozano, Gustavo A.
Abstract: BASF, Linde and RWE Generation have continued the investigations on the formation mechanism of aerosol-based emissions as a part of their ongoing joint development programme at the post-combustion capture pilot plant at Niederaussem. This paper summarises the results of the testing programme under real power plant operating conditions regarding the impact of solid particles in the flue gas on the formation of emissions, the effects of a wet electrostatic precipitator and other flue gas treatment technologies.